579-P: Exercise Upregulates Extracellular Vesicles (EVs) Proteins Involved in Immunomodulatory and Mitochondrial Pathways in Human Subjects - VAMVINI, MARIA; NIGRO, PASQUALE; GOODYEAR, LAURIE; MIDDELBEEK, ROELAND J.W. (Diabetes (New York, N.Y.), 2023)
Emerging data suggest that single bouts of exercise increase circulating hormones, cytokines, and EVs, and that these circulating factors may play a fundamental role in the beneficial effects of exercise on health. Here, we identify circulating factors in response to both acute exercise and exercise training and determine the effects of nutritional status on these responses. Blood samples were first collected before and immediately after an acute bout of maximal exercise in healthy, lean subjects (N=8, 3M/5F; age=27±2, V̇O2peak=28.4±1.2ml/kg/min). Subjects then completed a 10 wk moderate-intensity aerobic exercise training program (up to 65-70% VO2peak, 4x/week) with the same post-training sample collection. Proteomics (SOMAscan) quantified 1,310 circulating factors. In the untrained state, acute exercise upregulated 196 proteins and after training exercise upregulated only 65 proteins, with 47 proteins simultaneously upregulated in both the untrained and trained state. Interestingly, cellular component analysis showed that 1/3 of these shared proteins are localized in EVs. Next, we determined the baseline effects of exercise training in the fed and fasted state in the absence of acute exercise. Training upregulated 220 and 178 proteins in fed and fasted state, respectively. Exercise training commonly upregulated 120 proteins in the fed and fasted state with 1/3 localized in EVs. Integration using Vesiclepedia of the upregulated proteins in all 4 comparison groups showed 3 upregulated proteins in both acute exercise and training regardless of nutritional status: PPIF, PTPN6, and CLEC1B. These proteins are found in macrophages and neutrophils, and mediate immunomodulatory effects, promote tissue remodeling, and mitochondrial function. As EVs deliver molecules to cells altering their metabolism, they may play an important role in mediating the beneficial effects of exercise and warrant further mechanistic studies.